Effect of Cryptocurrency on Inflation in Nigeria: Economics - BadamasiSani Mohammed; Sule Ya’u Hayewa; Hussaini Shuaibu; Nuruddeen Mahmud Bunu (International Economic and Finance Review, 2022)
With the iconic move of demonetization, a drastic change is seen in the payment methods of the people. Now, the government wants its citizens to adopt new methods, thus, Nigeria has also triggered its next move to usher itself into the era. Therefore the aim of this paper is to examine the effect of cryptocurrency on inflation in Nigeria. The paper applied Vector Auto-regression (VAR) to analyze multivariate time series data for the period of 2009Q1 to 2021Q4. The finding from impulse response shows that, cryptocurrency account for a positive response to inflation in the first three periods and a negative response in the remaining periods, while money supply account a positive response throughout the periods. However, the results from variance decomposition show that cryptocurrency account for little variation in the inflation throughout the periods but money supply account for high variations of the inflation. Based on the findings, the paper recommends that, in order to reduce the level of inflation in the country, money supply should be curtailed by the monetary authority. Keywords: Cryptocurrency, Inflation, Money supply, Vector Auto-regression